An Implicit Algorithm for Maximal Monotone Operators and Pseudocontractive Mappings - Hong-Jun Li; Yeong-Cheng Liou; Cun-Lin Li; Muhammad Aslam Noor; Yonghong Yao (Abstract and Applied Analysis)
The purpose of this paper is to construct an implicit algorithm for finding the common solution of maximal monotone operators and strictly pseudocontractive mappings in Hilbert spaces. Some applications are also included.